ANALISIS PELAKSANAAN KURIKULUM 2013 PADA PEMBELAJARAN SENI RUPA DI SMA NEGERI 10 PADANG - Mita Sri Ganti; Zubaidah Zubaidah (Turast: Jurnal Penelitian dan Pengabdian, 2022)
This study aims to analyze the implementation of the 2013 Curriculum in art learning and the constraints in art learning based on the 2013 Curriculum at SMA Negeri 10 Padang in the Academic Year of 2022/2023. The type of research used is qualitative research with a descriptive approach. Informants in this study were the deputy head of the curriculum, art and culture teachers in the field of fine arts, and representatives of each class XI student who had studied art at SMA Negeri 10 Padang. Data collection techniques used are observation, interviews, and documentation. Based on data processing, it is known that the implementation of art learning at SMA Negeri 10 Padang in the preparation of the Rencana Pelaksanaan Pembelajaran (RPP) is in accordance with the 2013 Curriculum, but in the visual arts learning process the teacher has not used various learning strategies and there are still many students with low learning outcomes. . There are several obstacles that come from learning strategies, the delivery of learning that has not been completed by teachers, and teaching media facilities that are not used by teachers.